Pengaruh Islam Terhadap Pengamalan Keagamaan Masyarakat Di Indonesia - Mustaqim Hasan; Anita Anita (AT-THARIQ: Jurnal Studi Islam dan Budaya, 2022)
Islam entered Indonesia in general can be accepted by the Indonesian people by means of da'wah that brings peace without violence so that it is easy to develop and penetrate the soul, mind and behavior so that it is actualized in every activity of daily life into active religious practice which has become a tradition.This paper aims to find out how Islam can influence and what is affected by community religious practice activities in Indonesia. This research is a literature study that reveals a social phenomenon that occurs in society which is presented with a descriptive narrative as the author's study and experience.The influence of Islam in Indonesia has been seen since the beginning of its arrival in the early 7th century which was marked by the presence of Muslim villages in the Baros area of North Sumatra, but its influence has not been so widely seen, this is influenced by several obstacles that come from da'wah methods that have not been able to see local wisdom. Islam began to have a major influence on the religious practice of the Indonesian people, starting from the 13th century where the preachers with their wisdom combined local wisdom with the glory of Islam so that they were able to attract public sympathy. Among the influences of Islam in the religious activities of the Archipelago Community are: 1) The influence of the belief system has an impact on the worship activities of the people who used to adhere to animism and dynamism; 2) the influence of the social system, where the community used to still adhere to the caste system turned into a populist and kinship system. 3. Politics and government that adopts the sultanate system and the basis for making legal policies based on Islamic rules in the Qur'an and hadith; 4) Art and Literature influenced by styles and motifs from the Middle East.Keywords: Influence of Islam, Religious Practice